Analisis Kepribadian Tokoh Utama dalam Cerpen Apakah Langit Akan Biru Hari Ini Karya Rizqi Turama - Ayu, Ratih (SM Institute, 2024)
This research aims to describe the personality analysis of the main character in the short story Will the Sky Be Blue Today by Rizqi Turama. The research was designed using qualitative research. Data was collected using the close reading method and analyzed using qualitative descriptive. The results of the research include first, the Id of the Main Character of the Short Story Will the Sky Be Blue Today, namely (a) Id Fitri's desire to rest for a moment and look at the sky, (b) Id Fitri's desire to get away from her mother-in-law, (c) Id Fitri creates sadness when her husband could not accompany his child to the hospital. Second, the Ego of the Main Character of the Short Story Will the Sky Be Blue Today, namely (a) Id Fitri creates a desire to get away from her mother-in-law, Ego Fitri realizes that she still has her child (b) Ego Fitri feels satisfaction when she feels freedom, (c) Ego Fitri choose to move away from home. Third, the Superego of the Main Character of the Short Story Will the Sky Be Blue Today, namely Fitri's Superego makes her refrain from crying or fighting her mother-in-law, (b) Fitri's Superego chooses to avoid problems.